The Effectiveness of an 8-Week Learning Recovery Curriculum Program on Improving Literacy and Numeracy among Grade 3 Students in Public Elementary Schools in the Bicol Region: An Educational Economics Perspective - Juliana, Juliana (PT. Batari Edu Calya, 2025)
Literacy and numeracy skills are foundational, supporting long-term learning outcomes and significantly impacting future individual economic productivity. This study aims to evaluate the effectiveness of the 8-Week Learning Recovery Curriculum Program in enhancing the literacy and numeracy skills of Grade 3 students in selected public elementary schools in the Bicol region. Employing a descriptive-correlational research design combined with a Systematic Literature Review (SLR) approach, data were collected from 331 students and 11 teachers across five elementary schools in four districts of the Bicol region. The results indicate a significant increase in the proportion of students classified as 'Grade Ready,' rising from 21% in the pre-test to 34% in the post-test. This study underscores the importance of data-driven, short-term educational interventions in supporting human resource development and promoting efficiency in educational budget allocation.